Biogenic synthesis, characterization, and biological activity of silver nanoparticles from Eurycoma longifolia and Luffa acutangula - Devi Nallappan (2016)
This thesis present a green chemistry method on synthesising silver nano particles using plant materials. Eurycoma Iongifolia and Luffa acutangula are well known medicinal plants in Asian countries. Silver nano particles (AgNPs) are nano sized metal coated particles which enhance normal biological efficacies due to its small size and large surface volume ratio. Biogenically synthesised AgNPs using plant extracts could amplify the normal antioxidant activity of plant extracts to higher activity. The first part of this experiment was synthesising AgNPs. The colour changed from light brown to dark brown which indicated the bioreduction of silver ion to AgNPs. The UV-Vis spectrum results of AgNPs synthesised using 5% of E.Iongifolia leaves, E.longifolia branches and L.acutangula leaves resembled the highest absorbance peak which fall in the range of interest, 400nm-500nm. XRD analysis of these three AgNPs showed face centered cubic (fcc) crystalline shape. FTIR-ATR of synthesised AgNPs showed functional groups that act as capping agent in bioreduction process. SEM analysis exhibited the shape and size of synthesised AgNPs. The DPPH and ABTS antioxidant assays showed that the biosynthesised AgNPs have significant antioxidant efficacy compared to plant extracts. This ensures that AgNPs can be promising antioxidant agents to overcome severe oxidation problems.